(untitled) (Vietnam Journal of Community Medicine, 2024)
Purpose: The intracorporeal anastomosis technique in laparoscopic colectomy surgery has advantages such as relatively less invasiveness, faster recovery after surgery, and shorter hospital stays and preserve the oncologic principles. The aim of this study was to evaluate the short-term outcomes of intraoperative anastomosis in laparoscopic colectomy surgery in Thong Nhat hospital. Method: We retrospectively reviewed all elective laparoscopic hemicolectomies with complete intracorporeal anastomosis performed at Thong Nhat Hospital between January 2021 and August 2023. Results: There were 22 men (56.41%) and 17 women (43.59%) with an mean age of 71 years (45-89 years). Mean BMI is 20.65 Kg/m2 (16.9 - 23.6 Kg/m2). There were no conversion to open surgery. Average operating time, estimated blood loss, and hospital stay were 262 minutes (120 - 480 minutes), 44 ml (20 - 100 ml), 13 days (7 - 48 days), respectively. The mean incision length is 4.8 cm (3 - 9 cm). The average time to restore intestinal circulation is 2.44 days (2 - 3 days). There were no complications during surgery. Postoperative complications accounted for 7.7%: 1 case of surgical wound infection (2.6%), 2 cases of anastomosis leak (5.1%). The mean number of harvested lymph nodes was 9 lymph nodes (8 - 41 lymph nodes), 79.5% of patients had lymph node metastasis. All cases had R0 resection. The average specimen length is 28 cm (20 -40 cm). Conclusion: The intraoperative anastomosis in laparoscopic colectomy surgery could be considered a safe and feasible technique for treatment of malignant tumor diseases with low complications rate, short incision length for extraction, faster recovery after surgery.